2022
DOI: 10.3390/electronics11223812
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Framework for Assessment of the Effects of Digital Technologies on Sustainability Accounting and Reporting in the European Union

Abstract: Sustainability accounting and reporting is an emerging area of accounting that is receiving increasing attention as a result of sustainability requirements. In this paper, we examine the effects of implementing digital technology on sustainability accounting and reporting. This research consists of an empirical study at the level of 21 European Union countries using data provided by Eurostat. Transversal research emphasizes the impact of digital technologies (cloud computing, Big Data, the Internet of things, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…The information collected for this study refers to enterprises with high and very high DIIs, enterprises that employ ICT specialists with tertiary education, enterprises using the The digital intensity index values represent the percentage of organizations with a high digital intensity level, calculated as a percentage of the total number of businesses. The variables selected for the emerging digital technologies and digital intensity characterization also consider similar studies by other authors [6,18,21,49,50], as shown in Table 1. This research aims to analyze the impact of new digital technologies and the types of AI technology on the DII, and to evaluate the effect of using AI technology in various economic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information collected for this study refers to enterprises with high and very high DIIs, enterprises that employ ICT specialists with tertiary education, enterprises using the The digital intensity index values represent the percentage of organizations with a high digital intensity level, calculated as a percentage of the total number of businesses. The variables selected for the emerging digital technologies and digital intensity characterization also consider similar studies by other authors [6,18,21,49,50], as shown in Table 1. This research aims to analyze the impact of new digital technologies and the types of AI technology on the DII, and to evaluate the effect of using AI technology in various economic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research [6,18,20,21,[48][49][50] into the most relevant emerging digital technologies that contribute to the digital transformation of companies, we collected and performed data analysis related to the DII, company expenditure on research and development, employee education, and emerging digital technologies used within organizations in the EU. The variables regarding emerging technologies (Internet of Things, cloud computing, and artificial intelligence) and their association with digitalization as pillars of Industry 4.0 were also used in the papers [18,21,48,50].…”
Section: Methodsmentioning
confidence: 99%
“…There is a need to develop technologies for a digital supply chain and procurement in a sustainable environment [35]. Digital transformation has great potential for creating and implementing sustainable solutions [36]. Ozkan-Ozen et al [37] present that Procurement 4.0 contributes to the development of sustainable procurement, and Bag et al [38], Felsberger and Reiner [39] and Kumar et al [40] present contributions to ecological, i.e., green, procurement.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The compilation of relevant indices compilation is widely used in studying the social effects of digital economy by virtue of its high data availability, breadth of content coverage, and accounting treatment of indicators, which is more advantageous (Zhao et al, 2020;Ma et al, 2022;Zhao et al, 2023). According to the published articles, we use the comprehensive index evaluation method to measure the level of digital technology development at the city level (Chen et al, 2022;Wang J. et al, 2023;Liu et al, 2022;Vaȓzaru, 2022;Chen Y. et al, 2023;Wang H. et al, 2023). Combining the availability of city-level data, this paper measures the comprehensive development level of digital technology in each city from five aspects: broadband Internet foundation, mobile Internet foundation, information industry factor inputs, telecommunication industry output, and digital inclusive finance.…”
Section: Core Explanatory Variablementioning
confidence: 99%